1999
DOI: 10.2165/00003088-199937030-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Food on Clinical Pharmacokinetics

Abstract: Food-drug interactions can be associated with alterations in the pharmacokinetic and pharmacodynamic profile of various drugs that may have clinical implications. The various phases in which food may interact with a coadministered drug are: (i) before and during gastrointestinal absorption; (ii) during distribution; (iii) during metabolism; and (iv) during elimination. Absorption and metabolism are the phases where food has most effect, and this review will focus on those areas. It will also review the variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
245
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(257 citation statements)
references
References 371 publications
9
245
0
3
Order By: Relevance
“…Pharmacokinetic reactions, in which food affects the absorption, distribution, metabolism, or elimination of a drug, are the most commonly observed food-drug interactions [16]. For example, concomitant intake of food can affect the rate and extent of drug absorption from the gastrointestinal tract, resulting in reduced, delayed, increased, or accelerated drug absorption [17]. In addition, the influence of food is largely dependent on the pharmaceutical formulation of a specific drug, such that food intake with some extended-release drug formulations can substantially alter the release of the drug, which ultimately alters the drug absorption time profile and, thus, the overall clinical effect [17].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic reactions, in which food affects the absorption, distribution, metabolism, or elimination of a drug, are the most commonly observed food-drug interactions [16]. For example, concomitant intake of food can affect the rate and extent of drug absorption from the gastrointestinal tract, resulting in reduced, delayed, increased, or accelerated drug absorption [17]. In addition, the influence of food is largely dependent on the pharmaceutical formulation of a specific drug, such that food intake with some extended-release drug formulations can substantially alter the release of the drug, which ultimately alters the drug absorption time profile and, thus, the overall clinical effect [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, food intake triggers physiological changes in the gastric pH, changes in GI motility, etc., which can have profound impact on drug absorption (40). Food can also impact specific transporters that are involved in absorption of a drug.…”
Section: Impact Of Food On Bementioning
confidence: 99%
“…Taking lipophilic drugs with a high-fat meal is also known to increase their rate of dissolution [6]. Abiraterone acetate (AA), an orally available, highly lipophilic drug [7], is approved for the treatment of metastatic castration-resistant prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chi et al reported that in healthy subjects administered the OAA formulation, the area under the plasma concentration-time curve (AUC) and maximum measured plasma concentration (C max ) of abiraterone, the active metabolite of AA, increased by 10-and 17-fold, respectively, when given shortly after a high-fat meal relative to the fasted state [10]. Biorelevant in vitro studies suggest that intestinal fluids, such as bile salt [6,10] produced during the fed state, may facilitate the absorption of abiraterone, thus producing the food effect observed in pharmacokinetic trials [9]. The large bioavailability changes recognized in the reference product with regard to meal fat content [10] may lead to differences in safety, tolerability, and efficacy.…”
Section: Introductionmentioning
confidence: 99%